Synthesis and Characterization of UiO-66 as a Paracetamol Absorption Material - Fery Eko Pujiono; Try Ana Mulyati (Al-Kimia, 2019)
UiO-66 synthesis has been carried out by dissolving 0.53 grams of zirconium tetrachloride (ZrCl4) and 0.34 grams of Benzene-1,4-dicarboxylic Acid (H2BDC) in 30 mL Dimethylformamide (DMF). The solution is then distilled for 30 minutes and then heated in an oven at 140 ° C for 6 hours. The UiO-66 material produced was then characterized by an X-Ray Diffractometer (XRD) and Fourier Transform Infrared (FTIR). The results showed that the UiO-66 was successfully synthesized which supported the XRD results at 2θ 7.3o, 8.49o and 25.8o which were the peak characteristics of UiO-66. In addition, the FTIR results show a peak of around 1500 cm-1 showing vibrations of C = C on the benzene ring and a peak of about 1390 cm-1 indicating streching of O-C-O produced from the ligand. The peaks are around 750, and 660 cm-1 which indicates the presence of C-H vibrations from the ligand. UiO-66 was also approved as the adsorption agent of paracetamol which was approved with the highest adsorption of paracetamol at 72 hours immersion time which was 97.03%.